Potential Role of Lisinopril in Reducing Atherosclerotic Risk: Evidence of an Antioxidant Effect in Human Cardiomyocytes Cell Line - Scisciola, Lucia; Fontanella, Rosaria Anna; Surina,; Garofalo, Giovanna; Rizzo, Maria Rosaria; Paolisso, Giuseppe; Barbieri, Michelangela (Frontiers in Pharmacology, 2022)
The cellular mechanisms involved in myocardial ischemia/reperfusion injury (I/R) pathogenesis are complex but attributable to reactive oxygen species (ROS) production. ROS produced by coronary endothelial cells, blood cells (e.g., leukocytes, platelets), and cardiac myocytes have the potential to damage vascular cells directly and cardiac myocytes, initiating mechanisms that induce apoptosis, inflammation, necrosis, and fibrosis of myocardial cells. In addition to reducing blood pressure, Lisinopril, a new non-sulfhydryl angiotensin-converting enzyme (ACE) inhibitor, increases antioxidant defense in animals and humans. Recently, it has been shown that Lisinopril can attenuate renal oxidative injury in the l-NAME-induced hypertensive rat and caused an impressive improvement in antioxidant defense system Wistar rats treated with Doxorubicin. The potential effect of Lisinopril on oxidative damage and fibrosis in human cardiomyocytes has not been previously investigated. Thus, the present study aims are to investigate the effect of different doses of Lisinopril on oxidative stress and fibrotic mediators in AC16 human cardiomyocytes along with 7 days presence in culture medium. The results revealed that AC16 human cardiomyocytes exposed to Lisinopril treatment significantly showed an up-regulation of proteins involved in protecting against oxidative stress, like Catalase, SOD2 and Thioredoxin, and a reduction of Osteopontin, and Galectin-3, critical proteins involved in cardiac fibrosis. Moreover, Lisinopril treatment induced an increment in Sirtuin 1 and Sirtuin 6 protein expression. Taken together, these findings demonstrated that in AC16 human cardiomyocytes, Lisinopril could protect against oxidative stress and fibrosis via the activation of Sirtuin 1 and Sirtuin 6 pathways.